Alterations Induced by Bangerter Filters on the Visual Field: A Frequency Doubling Technology and Standard Automated Perimetry Study. (20th January 2015) - Schiavi, Costantino; Tassi, Filippo; Finzi, Alessandro; Cellini, Mauro
Abstract : Purpose . To investigate the effects of Bangerter filters on the visual field in healthy and in amblyopic patients. Materials and Methods . Fifteen normal adults and fifteen anisometropic amblyopia patients were analysed with standard automated perimetry (SAP) and frequency doubling technology (FDT) at baseline and with filters 0.8 and 0.1. Results . With 0.1 filter in SAP there was an increase of MD compared with controls (−10.24 ± 1.09 dB) in either the amblyopic (−11.34 ± 2.06 dB;P < 0.050 ) or sound eyes (−11.34 ± 1.66 dB;P < 0.030 ). With filters 0.8 the PSD was increased in the amblyopic eyes (2.09 ± 0.70 dB;P < 0.007 ) and in the sound eyes (1.92 ± 0.29 dB;P < 0.004 ) compared with controls. The FDT-PSD values in the control group were increased with the interposition of the filters compared to baseline (0.8;P < 0.0004 and 0.1;P < 0.0010 ). We did not find significant differences of the baseline PSD between amblyopic eyes (3.80 ± 2.21 dB) and the sound eyes (4.33 ± 1.31 dB) and when comparing the filters 0.8 (4.55 ± 1.50 versus 4.53 ± 1.76 dB) and 0.1 (4.66 ± 1.80 versus 5.10 ± 2.04 dB). Conclusions . The use of Bangerter filters leads to a reduction of the functionality of the magno- and parvocellular pathway.